PENGARUH BOOK-TAX DIFFERENCES, ACCRUAL, DAN OPERATING CASH FLOW TERHADAP UPAYA PENGHINDARAN PAJAK - Dea Mustika Kusuma Wardani; Arif Nugrahanto (JURNAL PAJAK INDONESIA, 2022)
This study aimed to analyze the effect of firm’s book-tax differences, accrual, and operating cash flow to its tendency of tax avoidance measured by current effective tax rate proxy. Using manufacturing firms listed in Indonesia Stock Exchange as population, a purposive sampling method that had been applied in this study resulted in 72 firms (360 observations) as samples. This study also examined the moderating role of corporate governance using independent commissioner proxy. This study concluded that book-tax differences have significant positive influence on tax avoidance. Accrual shows no influence on tax avoidance, while operating cash flow shows negative significant influence on tax avoidance. The moderating model showed that independent commissioners which represent corporate governance fail to interfere with the influence of book-tax differences, accrual, and operating cash flow on tax avoidance.   Penelitian ini bertujuan untuk menganalisis pengaruh book-tax differences, accrual, dan operating cash flow terhadap tax avoidance pada perusahaan manufaktur yang terdaftar di Bursa Efek Indonesia (BEI). Pemilihan sampel penelitian menggunakan metode purposive sampling yang menghasilkan 72 perusahaan sampel dan 360 observasi. Selain itu, penelitian ini juga menguji peran moderasi corporate governance terhadap pengaruh book-tax differences, accrual, dan operating cash flow terhadap tax avoidance. Hasil penelitian menyimpulkan bahwa book-tax differences berpengaruh positif terhadap tax avoidance, accrual tidak berpengaruh terhadap tax avoidance, dan operating cash flow berpengaruh negatif terhadap tax avoidance. Sedangkan, corporate governance melalui proporsi komisaris independen tidak berhasil memoderasi pengaruh book-tax differences, accrual, dan operating cash flow terhadap tax avoidance.